Characterization of Flavonoid Aglycones in Aerial Parts of Hypericum oblongifolium L. - Saddiqe, Zeb; Naeem, Ismat; Mughal, Tahira; Taskeen, Abida; Mubeen, Hifsa (Asian Journal of Chemistry, 2010)
The genus Hypericum is known worldwide for its traditional and modern uses. Several species of this genus have been used in folk medicine. Extracts from a number of species of the genus were found to possess antifungal, antibacterial, antimalarial, antioxidant and antidepressant activities. The main constituents of these extracts are reported to be phloroglucinols and flavonoids. Hypericum oblongifolium L. is an important representative of the genus in the northern areas of Pakistan used in traditional herbal medicine. The present paper describes a simple, fast, specific and precise method coupling high-performance liquid chromatography (HPLC) with UV detection for the separation and identification of six flavonoid aglycons in the extracts of aerial parts of H. oblongifolium. Quercetin, myricetin, rhamnetin, isorhanmetin, kaempferol and luteolin were used as standards. The compounds were separated on a prepacked analytical C18 column (250 mm × 4.6 mm, 5 μm particle size) using acetonitrile/water 1:1 acidified with 1 % acetic acid as mobile phase. The flow rate was kept constant at 1.0 mL/min at 25 °C and the peaks were detected at 254 nm. The flavonoid content was expressed as quercetin equivalent and the quantification was by peak area measurement. The results showed that the most abundant flavonoid aglycones were luteolin (0.368 mg/g dry wt.) and myricetin (0.322 mg/g dry wt.) while isorhamnetin was not detected in this species.